PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DI SETDITJEN P2MKT DAN DIREKTORAT PKSM DIREKTORAT JENDERAL P2MKT, KEMENAKERTRANS JAKARTA TAHUN 2014 - Nahda Nahda (KENEGARAAN, 2016)
The object of research phenomon is the employee’s job performance who is not optimally to be influenced to make a policy and implementation of policy. The employee’s job performance who is not optimal indicated that input of dimension with base of idea to critical attitude which is almost focus to lowest of state employee have lowest and such input of dimension is job discipline and compensation. The aim of research is to know both discription and analysis for an influencing job discipline and compesation toward job performance either partial or simulant. The type of research is descriptive quantitative. The result of research have multiple regression linear : Y = 17.957 + 0.183Xi 0,799X, the assumption, if the job discpline and compensation variables are stagnant, thus job performance variable shall be valued 17.957. In the other hand, coeficient value of job discipline is 0.183 stated that, if one score is job discipline would be increased the job performance is 0.183. Compensation value indicated 0.799 stated that, one score of compensation would be increased the job performance is 0.799. Coeficient of determination (R22) is 0.754 or 75.4%. This meant that, 75.4% dependent variable (job performance) affected by independent variables (job discipline and compensation). In the other hand, the residual 24.6% clarified by another variables behind of subject variables.